1997
DOI: 10.1128/jcm.35.1.239-242.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ligase chain reaction and culture for detection of Neisseria gonorrhoeae in genital and extragenital specimens

Abstract: In addition to the urogenital tract, Neisseria gonorrhoeae infects extragenital sites such as the pharynx and anorectal canal. Culture and a ligase chain reaction (LCR)-based assay were compared for their performance for the diagnosis of N. gonorrhoeae infection with specimens from various urogenital and extragenital sites of 200 men and 125 women. The sensitivity and specificity of the LCR assay with male urethral swabs were both 100%, compared to values of 95.9 and 100%, respectively, for culture of urethral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…In general, NAATs have a higher sensitivity than culture especially for samples from the rectum and pharynx (21, 73–76). However, NAATs based on detection of genes on the cryptic plasmid, e.g.…”
Section: Laboratory Diagnosis Of Neisseria Gonorrhoeaementioning
confidence: 99%
“…In general, NAATs have a higher sensitivity than culture especially for samples from the rectum and pharynx (21, 73–76). However, NAATs based on detection of genes on the cryptic plasmid, e.g.…”
Section: Laboratory Diagnosis Of Neisseria Gonorrhoeaementioning
confidence: 99%
“…In contrast, the prevalence of chlamydia seems to vary widely across and within regions-from below 5 percent to around 25 percent in all regions. have emerged as the standard tests for chlamydia, with sensitivity and specificity better than those from culture (Buimer et al 1996;Gray and Wawer 1996;Puolakkainen et al 1998;Stary et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported similar findings. 5,6 Differences in the racial/ethnic, age, and regional distribution of incident and prevalent AIDS cases reflect some differences in historical patterns of HIV incidence. Those include the later onset of the HIV epidemic in the South compared with the West and the Northeast, and the increasing impact on racial/ethnic minorities.…”
Section: Interviews Of Msm/idumentioning
confidence: 99%